"Sustainable" biomass: A paper tiger when it comes to reducing carbon emissions. (4th May 2022) - Booth, Mary S.
ABSTRACT: As the tragedy in Ukraine deepens, it's clear that the world should end its dependency on Russian oil. It will be ironic, however, if nations disentangling themselves from this compromised energy source instead turn to another energy source with destructive impacts: harvesting and burning forest wood for fuel, which increases carbon emissions compared to fossil fuels, and degrades forests.